Mechanistic study of surface functionalization of enzyme lysozyme synthesized Ag and Au nanoparticles using surface enhanced raman spectroscopy - Das, Raja; Jagannathan, Ramya; Sharan, Chandrashekhar; Kumar, Umesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
The fate of bioactivity of biomolecules such as enzymes, proteins, and even drug molecules is greatly affected by the conformational changes in the proximity of the solid surfaces. This interaction is the key to the potential of their further applications as biosensors, in drug delivery, etc. With increasing interest in the biofunctionalization of noble metal nanoparticles for various applications, it is important to precisely investigate the functional groups responsible for binding with the nanoparticle surfaces and probable structural changes in the structure of the biomolecules as both are key factors affecting the bioactivity of these molecules once they are tagged onto the nanoparticle surfaces. However, it is not an easy task to probe these properties, especially for bigger Molecules such as enzymes and proteins. Surface-enhanced Raman spectroscopy (SERS) has been used extensively in the detection of biomolecules and study of their conformation on noble metal surfaces since its discovery because of its high sensitivity. This technique is capable of detecting changes in the secondary structure and the effects of surrounding environment on the biomolecule in the proximity of nanoscopic rough metal surfaces. In this study, we have used this technique to precisely determine the functional groups responsible in the Surface capping of Ag and Au nanoparticles synthesized by the hen egg derived enzyme lysozyme. The sharp and intense Stokes Raman shift peaks observed around 704, 866, 1519, and 1598 cm(-1), in the case of Ag nanoparticles, which are assigned to tryptophan, tyrosine, phenylalanine, and histidine residues, clearly indicate the involvement of these residues for surface passivation of the Ag nanoparticle surface. The Ag-N peak situated around 236 cm(-1) was also seen in the spectra, showing that probably the amine group of lysozyme is responsible in binding to the Ag nanoparticle surface. Similarly, in the case of Au nanoparticles, we observed sharp and intense peaks around 1583, 1545, and 1584 cm(-1) which were assigned to above-mentioned amino acid residues, indicating that a similar mechanism is also responsible for the binding of lysozyme molecules at the Au nanoparticle surface. In both cases peaks for the amide III band (C-N-H) around 1250 cm(-1) were also observed.

Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver

Photopatternable nano-composite (SU-8/ZnO) thin films for piezo-electric applications - Kandpal, Manoj; Sharan, Chandrashekhar; Poddar, Pankaj; Prashanthi, K.; Apte, Prakash R.; Rao, V. Ramgopal (Applied Physics Letters, 2012)
Photo-curable nanocomposite material was formulated by embedding ZnO nanoparticles into a SU-8 matrix and studied for its piezoelectric properties for low cost fabrication of self-powered nanodevices. The piezoelectric coefficient of ZnO nanoparticles was observed to be ranging between 15 and 23 pm/V, which is the highest reported. These experimental studies support the recent theoretical predictions where the piezoelectric coefficients in ZnO nanoparticles were found to be higher compared to the thin films because of the surface relaxation induced volume reductions in the nanometer scale. The photo-curable property of these polymer composite films is exploited to demonstrate fabrication of a micro-cantilever test structure. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4748575]

Biomilling of rod-shaped ZnO nanoparticles: a potential role of saccharomyces cerevisiae extracellular proteins - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
There is a tremendous interest in newly-discovered, green, room-temperature, biological routes for the fabrication of biologically-benign functional nanostructures. The bottom-up biogenic synthesis, where the precursor molecules form crystalline solids at the nanoscale by a redox process, has been validated over the years and gained its popularity. However, a new top-down technique has recently been developed by our group, in which small isotropic nanoparticles (NPs) are formed by the break-down of chemically-synthesized anisotropic rod or plate-shaped NPs using microbes (termed as biomilling). This technique, which holds great promise, is still in its infancy. Here, an improved process with an easy isolation of NPs from the biomass and better control of the technique is reported. This novel technique is demonstrated to break-down the chemically synthesized ZnO nanorods (NRs), similar to 250 nm in length, to small quasi-spherical ZnO NPs (similar to 10 nm in diameter) possibly due to the proteins secreted by the yeast (Saccharomyces cerevisiae), which also led to the formation of `` corona'' around the NPs. The UV-vis, PL and FTIR results show the dynamic nature of the protein corona, which is further supported by the SDS-PAGE study of the extracellular proteins. The SDS-PAGE study of the intracellular proteins shows the over-expression of a single protein which is supposed to have a role in zinc transport in the cells. The ICP-OES results show the accumulation of a higher amount of zinc in the yeast cells as biomilling progresses, while the extracellular zinc contents were almost same. Therefore, we believe that the yeast cells play an important role in the biomilling process by secreting the proteins and maintaining the zinc content in the extracellular fluid. The biomilled NPs exhibit a uniform dispersity and better aqueous stability than chemically synthesized ZnO NRs.

Mechanistic insight into the biomilling of goethite (alpha-FeO(OH)) nanorods using the yeast Saccharomyces cerevisiae - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
Since the last decade, eco-friendly routes for the synthesis of nanostructured materials of various types and functionalities have been a topic of enormous interest in the field of nanotechnology. The primary work in this field started with the `bottom-up' microbial synthesis of nanoparticles, however, the bioleaching potential of microbes was initially overlooked in this research. The bioleaching process is useful especially where the synthesis of particles with size < 10 nm is challenging. In the present work, the mechanistic insight of biomilling for a gradual transformation of anisotropic alpha-FeO(OH) rod-shaped particles into isotropic nanoparticles below 10 nm size has been explored using detailed UV-vis spectroscopy, transmission electron microscopy, atomic force microscopy, X-ray diffraction, and X-ray photoelectron spectroscopic studies which suggest that the aquo group present at the alpha-FeO(OH) surface may provide the site for interaction with carboxyl ions of protein molecules which results in the formation of a stable coordination compound with Fe3+ ions. This will create a new Fe3+ ion on the surface of the lattice which leads to the repetition of the process of protein complexation with Fe3+ ions and dissociation of the complex from the lattice that causes the fragmentation of bigger nanoparticles into protein functionalized smaller nanoparticles.